The Role of Teachers as Learning Motivators for Pekanbaru Elementary School Students - Wulandari, Putri; Mustika, Dea (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the role of the teacher as a motivator in student learning in elementary schools. The method used in this research is descriptive qualitative. Data collection techniques and instruments are interviews, observation, and documentation. Testing the validity of the data used source triangulation and technique triangulation. The data analysis technique used is data reduction, data presentation, and conclusions. This study concludes that the teacher's role as a learning motivator includes three indicators. The first is to arouse students' interest, and the second is to clarify the goals. The third is to create a pleasant atmosphere for learning. Overall the teacher has tried to carry out his role as a motivator for student learning in learning even though the teacher has not shown maximum results. Constraints The teacher acts as a motivator in learning; namely, the obstacles experienced by the teacher are not too heavy such as communicating with students is still tricky because many students are noisy in the class so that when explaining learning material, it is not heard clearly by students who sit behind. However, the teacher always tries to help students follow the learning in class well.